Strategi Digital Marketing dan Brand Awareness Dalam Meningkatkan Keputusan Pembelian Produk Beras Kita di Perum Bulog Bandung - Reza Fauzi Bukhori; Indra Herdiyana Sudrajat (KarismaPro, 2024)
This study uses descriptive and verification methods with a quantitative approach or in the form of numbers. The population in this study were customers of Perum Bulog Subdrive Regional Bandung as many as 410 customers. And sample  in this study were customers of Perum Bulog Subdrive Regional Bandung as many as 80 coustemers. The analysis used is Path Analysis of find out. And indirectly to other variables. The result of this study indicate that: (1) digital marketing has a significant positive effect on the purchasing decision at Perum Bulog Subdrive Regional Bandung is 41.7%. (2) brand awareness commitment has a significant positive effect on the buying decision at Perum Bulog Subdrive Regional Bandung is 14%. The total influence of the variable digital marketing and brand awareness on the srtuctural model buying decision is shown by the magnitude of the coefficient of determination r2 = 0.559 or 55.9%, while the influence of outside variables or errors is 44.1%Based on the result of the above research, it can be concluded that the model formed belongs to the strong category so that in this study variables of digital marketing and brand awareness are precisely used to measure the purchasing decision of customers at Perum Bulog Subdrive Regional Bandung. The  44.1% variables that were not examined inclued advertising, public relations, sales promotion, brand image, product quality, etc.